JPHYD Inhibits miR-21-5p/Smad7-Mediated Epithelial-Mesenchymal Transition of Hepatocellular Carcinoma Cells. (26th April 2022) - Liu, Li-Hua; Fang, Chong-Kai; Ge, Fu-Cheng; Wang, Ji-Nan; Zhang, Xiu-Bing; Luo, Rui; Zhang, Ying; Feng, Kun-Liang; Qiu, Zhen-Wen; Zhong, Chong
Abstract : Background. Studies have shown that Jianpi Huayu Decoction (JPHYD) can inhibit the growth of hepatocellular carcinoma cells, but the mechanism of its effect was not clear at present. Methods. We assessed the effect of JPHYD using liver cancer cells as in vitro cell model and xenograft tumor as in vivo model. CCK8, EdU, wound-healing, and transwell assays were performed to assess the cell growth, migration, and invasion of hepatocellular carcinoma (HCC) cell lines HepG2 and MHCC97H. Western blot assay was performed to observe the protein level of E-cadherin, Smad7, N-cadherin, Snail, Smad3, Vimentin, and Zeb1. qRT-PCR assay was used to observe the expression of miR-21-5p in clinical liver cancer tissue samples and in HepG2 and MHCC97H cells. Animal tumorigenesis experiments and in vivo imaging experiments were performed to assess the results of in vitro experiments. Results. We found that JPHYD could inhibit the proliferation, invasion, and migration of hepatocellular carcinoma cells and JPHYD decreased the level of N-cadherin, Snail, Vimentin, Smad3, and Zeb1 and increased E-cadherin and Smad7 proteins. The expression of miR-21-5p was increased while that protein of Smad7 was decreased in HCC tissues. The vivo experiments also showed that miR-21-5p could promote the migration of HCC cells. JPHYD decreased miR-21-5p expression. The same results have been found in animal studies. Conclusion. Our results indicated that JPHYD inhibited epithelial-mesenchymal transition by increasing Smad7 expression and inhibiting miR-21-5p. Therefore, blocking the occurrence and development of EMT may be a new mechanism of JPHYD's anti-liver cancer effect.